Characterization of Density and Stability of Oil Palm Empty Fruit Bunch Briquettes without Binder under Variations of Molding Temperature and Compaction Pressure - Muhammad Ravi Albasyit; Yolli Fernanda; Refdinal Refdinal; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
The dependence on fossil fuels in Indonesia continues to increase in line with the growing energy consumption, thus necessitating alternative energy sources that are more environmentally friendly and sustainable. Oil palm empty fruit bunches (OPEFB) are agro-industrial waste with great potential to be utilized as raw material for briquette production; however, their utilization remains suboptimal. This study aims to analyze the effect of molding temperature and compaction pressure on the density and stability of binderless OPEFB briquettes. The research method employed is experimental, using a quantitative descriptive-analytical approach with non-carbonized briquettes. The treatment variations include molding temperatures (230°C, 250°C, and 280°C) and compaction pressures (1 MPa, 3 MPa, and 5 MPa) applied to two types of materials, namely dried and undried OPEFB. The results indicate that increasing temperature and compaction pressure significantly enhances briquette density. At a temperature range of 250–280°C and a pressure of 5 MPa, the briquettes achieved the highest density (>1.0 g/cm³) with strong shape stability. The thermoplastic lignin content in OPEFB melts at high temperatures, acting as a natural binder. Briquettes with a density ?0.80 g/cm³ exhibited strong physical integrity, while those with a density <0.70 g/cm³ tended to be brittle. It can be concluded that the optimum conditions for producing high-quality binderless OPEFB briquettes are achieved at a temperature range of 250–280°C and a compaction pressure of 5 MPa, resulting in briquettes with excellent density and shape stability suitable as a renewable alternative energy source